Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure! Let's solve the system of linear equations step by step.
Given the system of equations:
[tex]\[ \begin{cases} 3x - 5y = 16 \\ 2x + y = 15 \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
We can solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x + y = 15 \implies y = 15 - 2x \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the first equation
Now we'll substitute [tex]\( y = 15 - 2x \)[/tex] into the first equation:
[tex]\[ 3x - 5(15 - 2x) = 16 \][/tex]
### Step 3: Simplify and solve for [tex]\( x \)[/tex]
Expand and simplify the equation:
[tex]\[ 3x - 75 + 10x = 16 \implies 13x - 75 = 16 \implies 13x = 91 \implies x = \frac{91}{13} \][/tex]
So,
[tex]\[ x = 7 \][/tex]
### Step 4: Substitute [tex]\( x \)[/tex] back to find [tex]\( y \)[/tex]
Now we use [tex]\( x = 7 \)[/tex] in the equation [tex]\( y = 15 - 2x \)[/tex]:
[tex]\[ y = 15 - 2(7) \implies y = 15 - 14 \implies y = 1 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (7, 1) \][/tex]
So the answer is:
[tex]\[ (x, y) = (7, 1) \][/tex]
Given the system of equations:
[tex]\[ \begin{cases} 3x - 5y = 16 \\ 2x + y = 15 \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
We can solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x + y = 15 \implies y = 15 - 2x \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the first equation
Now we'll substitute [tex]\( y = 15 - 2x \)[/tex] into the first equation:
[tex]\[ 3x - 5(15 - 2x) = 16 \][/tex]
### Step 3: Simplify and solve for [tex]\( x \)[/tex]
Expand and simplify the equation:
[tex]\[ 3x - 75 + 10x = 16 \implies 13x - 75 = 16 \implies 13x = 91 \implies x = \frac{91}{13} \][/tex]
So,
[tex]\[ x = 7 \][/tex]
### Step 4: Substitute [tex]\( x \)[/tex] back to find [tex]\( y \)[/tex]
Now we use [tex]\( x = 7 \)[/tex] in the equation [tex]\( y = 15 - 2x \)[/tex]:
[tex]\[ y = 15 - 2(7) \implies y = 15 - 14 \implies y = 1 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (7, 1) \][/tex]
So the answer is:
[tex]\[ (x, y) = (7, 1) \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.